Graphene modified gradient distribution high-temperature-resistant anticorrosive paint and preparation method thereof

The high temperature resistant anticorrosive coatings distributed through graphene modified gradients solve the problem of unstable performance of existing coatings in high temperature environments, realize high adhesion, high temperature resistance and corrosion resistance, and provide long -term effective protection effects.

CN119371873AActive Publication Date: 2025-01-28ZHEJIANG UNIV +1

Patent Information

Application Number
CN202411628165.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing high-temperature anti-corrosion coatings have unstable performance in high-temperature corrosion environments, short effective protection life, and poor compatibility between thermosetting resins and thermoplastic resins lead to phase separation and produce defects.

Method used

High temperature resistant anticorrosive coatings distributed with graphene modified gradients, which include graphene thermoplastic resin additives, organic silicon hybrid epoxy resin base materials, and amino silicohlor. Distributed coating.

Benefits of technology

The high attachment of coating, excellent high temperature resistance and corrosion resistance, extending the curing time and high temperature stability of the coating, and providing long -term effective protective effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371873A_ABST
    Figure CN119371873A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene modified gradient distribution high-temperature-resistant anticorrosive coating and a preparation method thereof. The anticorrosive paint comprises a graphene thermoplastic resin additive, an organic silicon hybrid epoxy resin base material and a curing agent, the graphene thermoplastic resin additive is prepared from the following components in parts by mass: 45 to 59 parts of xylene, 40 to 50 parts of aromatic resin, 0.05 to 1 part of modified graphene oxide and 0.5 to 2.5 parts of fumed silica. The organic silicon hybrid epoxy resin base material comprises the following components in parts by mass: 50-80 parts of organic silicon hybrid epoxy resin, 1-5 parts of n-butyl alcohol, 1-5 parts of butyl acetate, 5-20 parts of hollow glass beads, 3-15 parts of titanium dioxide, 3-15 parts of mica iron oxide and 0.5-8 parts of modified bentonite. The organic-inorganic hybrid high-temperature-resistant anticorrosive coating disclosed by the invention can be used for cold spraying construction and has high adhesive force and excellent high-temperature resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high temperature resistant anti-corrosion coatings, and specifically relates to a graphene modified gradient distributed high temperature resistant anti-corrosion coating and a preparation method thereof. Background Art

[0002] In the fields of aviation, aerospace, and shipbuilding, a large number of core components and key structural parts of high-end equipment are under high-temperature working conditions for a long time. Their operating status directly restricts the operating stability of aircraft, spacecraft, or aircraft. Therefore, the research on high-temperature resistant anti-corrosion coatings has attracted more and more attention at home and abroad. Cold sprayed organic coatings have the characteristics of high bonding strength with the substrate, convenient construction, and wide application, but they face problems such as unstable performance and short effective protection life in high-temperature corrosion environments. This is because thermosetting resins are easily oxidized and thermally decomposed under high temperature conditions, which leads to cracking or peeling of the coating; while thermoplastic resins are prone to softening, melting, and flowing under high temperature conditions, causing the coating to desorb from the substrate surface and lose its protective effect on the substrate. The combination of thermosetting and thermoplastic resins to prepare coatings can use the fluidity of thermoplastic resins to eliminate the shrinkage internal stress of thermosetting resins to a certain extent, and even the melting and flow of thermoplastic resins can repair the cracking and glass formation of the coating; while thermosetting resins can slow down the fluidity of thermoplastic resins under high temperature conditions, so that they maintain morphological stability. However, thermosetting resins and thermoplastic resins usually face the problem of poor compatibility, which makes it very easy for the two to form phase separation in the coating and generate defects.

[0003] In order to solve the above problems, it is urgent to develop new cold spray organic coatings to meet the requirements of high temperature resistance, corrosion resistance and long life. Graphene, as a two-dimensional carbon nanomaterial, has excellent properties such as high electrical and thermal conductivity, high light transmittance and high shielding. By grafting oxygen-containing groups such as hydroxyl, carboxyl and epoxy groups on the surface of graphene to form graphene oxide, various properties of graphene can be effectively regulated, giving it a wider range of applications. Summary of the invention

[0004] The purpose of the present invention is to provide an organic-inorganic hybrid high-temperature resistant anti-corrosion coating which can be cold-sprayed and has high adhesion, excellent high-temperature resistance and corrosion resistance. To this end, the present invention also provides a method for preparing the anti-corrosion coating.

[0005] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0006] The invention provides a graphene-modified gradient-distributed high-temperature-resistant anticorrosion coating, which comprises a graphene thermoplastic resin additive, an organosilicon hybrid epoxy resin base material and a curing agent.

[0007] The mass fraction of the graphene thermoplastic resin additive component is: 45-59 parts of xylene, 40-50 parts of aromatic hydrocarbon resin, 0.05-1 part of modified graphene oxide, and 0.5-2.5 parts of fumed silica;

[0008] The mass fractions of the organosilicon hybrid epoxy resin base material components are: 50-80 parts of organosilicon hybrid epoxy resin, 1-5 parts of n-butanol, 1-5 parts of butyl acetate, 5-20 parts of hollow glass microspheres, 3-15 parts of titanium dioxide, 3-15 parts of mica iron oxide, and 0.5-8 parts of modified bentonite;

[0009] The mass fractions of the aminosilane curing agent component are: 1 to 5 parts of n-butanol, 1 to 5 parts of butyl acetate, and 90 to 98 parts of aminosilane coupling agent.

[0010] Another object of the present invention is to provide a method for preparing the above-mentioned coating, characterized in that the steps are as follows:

[0011] Step 1: Add graphene oxide, anhydrous ethanol and silane coupling agent to deionized water, and ultrasonically treat for 10 to 30 minutes at a power of 100 to 300 W to obtain a graphene oxide dispersion. Then place the above dispersion in a constant temperature oil bath of 50 to 80°C and stir continuously for 12 to 24 hours to obtain a modified graphene oxide solution. Use a microporous membrane with a pore size of 0.25 to 0.5 μm to filter the modified graphene oxide solution, and wash it with anhydrous ethanol for 5 to 10 times. Finally, place the modified graphene oxide wet cake in a vacuum drying oven at 40 to 60°C and dry it for 5 to 10 hours to obtain silane-modified graphene oxide;

[0012] Step 2: adding the silane-modified graphene oxide to a xylene solution, treating it under an ultrasonic action of 100 to 300 W for 0.5 hours to obtain a graphene oxide dispersion, then adding an aromatic hydrocarbon resin and an oleophilic fumed silica, and continuously stirring the mixture at a speed of 300 to 600 r / min for 0.5 to 2 hours in a constant temperature oil bath at 50 to 80° C. to obtain an additive;

[0013] Step 3: Mix the components of the organosilicon hybrid epoxy resin base material, and continuously stir at a speed of 300 to 600 r / min for 15 to 60 minutes at room temperature to obtain a base material;

[0014] Step 4: Mix the additives with the base material, stir continuously at a speed of 300 to 600 r / min at room temperature for 15 to 60 minutes, finally add the components of the curing agent, and stir continuously at a speed of 300 to 600 r / min at room temperature for 15 to 30 minutes to obtain a high temperature resistant anti-corrosion coating.

[0015] Step 5: Apply the above-mentioned high temperature resistant anti-corrosion coating on the substrate, dry it at room temperature for 12 to 60 hours to form a cured coating film, then increase the temperature from room temperature to 400 to 700°C at a heating rate of 3 to 15°C / min, and maintain it at 400 to 700±10°C for 2 to 8 hours to obtain a gradient distributed high temperature resistant anti-corrosion coating.

[0016] In step (1) of the present invention, the graphene oxide is lightly oxidized graphene, the number of which is 1 to 5 layers, the lateral equivalent diameter of the flakes is 0.5 to 5 μm, the oxygen-containing groups are one or a combination of hydroxyl, carboxyl, and epoxy groups, and the oxygen-to-carbon ratio ranges from 0.1 to 2, preferably from 0.2 to 0.5.

[0017] In step (1) of the present invention, the silane coupling agent is selected from one or any combination of γ-aminopropyltriethoxysilane, vinyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0018] In step (1) of the present invention, the amount of graphene oxide is 0.1% to 1% of the amount of anhydrous ethanol, preferably 0.2% to 0.5%; the amount of silane coupling agent is 0.1% to 10% of the amount of anhydrous ethanol, preferably 0.2% to 5%; the amount of water is 5% to 100% of the amount of anhydrous ethanol, preferably 10% to 50%.

[0019] In step (2) of the present invention, the aromatic hydrocarbon resin includes, but is not limited to, one or a mixture of C5 aliphatic petroleum resin, C9 aromatic hydrocarbon petroleum resin, DCPD cycloaliphatic diene resin, hydrogenated petroleum resin, and condensed polynuclear aromatic hydrocarbon resin.

[0020] In step (2) of the present invention, the primary particle size of the oleophilic fumed silica is 10 to 40 nm, and the surface grafted modifier includes but is not limited to one or a combination of the following: polydimethylsiloxane, dimethyldichlorosilane, hexamethyldisilazane, γ-aminopropyltriethoxysilane, and trimethoxypropylaminosilane.

[0021] In step (3) of the present invention, considering that the organosilicon hybrid epoxy resin must ensure both the integrity of the cured coating and a sufficiently high ratio of the high temperature resistant filler, the amount of the organosilicon hybrid epoxy resin in the base material is preferably 56 to 72 parts.

[0022] In step (3) of the present invention, considering that the coating must ensure both excellent high temperature resistance and good mechanical properties, the diameter of the hollow glass microspheres is preferably 50 to 200 μm, the wall thickness is preferably 1 to 2 μm, and the amount thereof is preferably 10 to 15 parts.

[0023] In step (3) of the present invention, in order to enable the coating to obtain excellent high temperature resistance, the size of the titanium dioxide added to the base material is preferably 100nm to 500nm, and the amount is preferably 5 to 10 parts.

[0024] In step (3) of the present invention, in order to ensure the excellent film-forming property and high temperature resistance of the coating, the mica iron oxide added to the base material preferably has a size between 50 μm and 200 μm, and the amount used is preferably 5 to 10 parts.

[0025] In step (3) of the present invention, in order to ensure the dispersion stability of various high-temperature resistant pigments and fillers added to the coating and the long-term stability of the high-temperature resistance and anti-corrosion properties of the coating, the amount of modified bentonite is preferably 1 to 5 parts, and the surface grafted modifier is preferably one or a combination of the following: dioctadecyl dimethyl ammonium chloride, glycidyl acrylate, dimethylaminoethyl methacrylate, 3-sulfonate propyl methacrylate potassium salt.

[0026] In step (4) of the present invention, in order to ensure that the coating forms a good gradient distribution after "secondary curing" and maintain the surface uniformity of the coating, the amount of the additive should be 20% to 40% of the base material, preferably 25% to 35%.

[0027] In step (4) of the present invention, in order to ensure rapid film formation of the coating and maintain good mechanical properties after "secondary curing", the amount of curing agent should be 22.5% to 30% of the base material, preferably 25% to 27.5%.

[0028] In step (5) of the present invention, in order to ensure uniform crosslinking and curing of the coating, it is preferably cured at room temperature for 24 to 48 hours, and then preferably increased from room temperature to 500 to 600°C at a heating rate of 5 to 10°C / min, and maintained at a temperature of 500 to 600±10°C for 2 to 5 hours.

[0029] The three-component graphene high temperature resistant anti-corrosion coating proposed in the present invention has good corrosion resistance, excellent adhesion and high temperature resistance. The coating can be cured and dried within 48 hours, the coating thickness is about 100-150μm, and it forms a gradient distribution and "secondary curing" under high temperature conditions, which can further improve the stability of the coating under high temperature conditions and form a long-term effective protection for metal substrates in high temperature environments.

[0030] The inventors have found through experiments that by directly adding aromatic resin to silicone epoxy resin coating, the aromatic resin will be distributed in the silicone epoxy coating in the form of phase separation. When the coating is placed in a high temperature environment, the aromatic resin will expand due to heat, while the silicone epoxy resin will solidify and shrink, which will lead to a more obvious phase separation phenomenon in the coating, and finally the coating will have a large number of cracks and peeling, and lose its effective protective effect on the substrate. Adding a small amount of modified graphene oxide to the coating according to the above steps can greatly improve the compatibility between the aromatic resin and the silicone epoxy resin, so that the two are fully integrated and become a whole in the coating. When the graphene oxide-modified coating is placed in a high temperature environment, the aromatic resin will evenly penetrate from the inside of the coating to the surface of the coating to form a gradient distribution, and further cross-link and solidify on the surface of the coating, and finally form pyrolytic carbon and glassy carbon layers. Pyrolytic carbon and glassy carbon layers have excellent high temperature resistance, corrosion resistance and heat insulation properties, thereby forming a high temperature protection effect on the underlying silicone epoxy coating.

[0031] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:

[0032] The use of modified graphene oxide eliminates the incompatibility between aromatic hydrocarbon resin and silicone epoxy resin, allowing the two to be evenly fused and form a good connection through graphene oxide, thereby obtaining excellent mechanical properties. The specific advantages of this coating are: (1) The thermosetting resin and the thermoplastic resin are combined and fully fused, so that the coating has the characteristics of high adhesion and high density, as well as excellent heat resistance and chemical stability; (2) During the high-temperature curing process, the silicone resin as a thermosetting resin continuously crosslinks and shrinks, while the aromatic hydrocarbon resin as a thermoplastic resin will melt and expand, so the aromatic hydrocarbon resin will migrate evenly from the bottom layer to the surface layer in the silicone resin matrix coating, and finally form a gradient distribution with strong binding force; (3) The modified graphene allows the aromatic hydrocarbon resin to be evenly distributed in the coating, and it can be evenly exuded under high temperature conditions, maintaining the structural integrity of the coating, and allowing the aromatic hydrocarbon resin to form a gradient distribution on the surface of the coating; (4) The modified graphene not only ensures the uniform distribution and (5) After the "secondary curing" of the coating surface, the aromatic resin forms a pyrolytic carbon and glassy carbon structure that is highly stable under high temperature and corrosive environment, which provides good protection for the underlying silicone resin and the protected substrate; (6) The gradient distribution of the aromatic resin under high temperature conditions enables the pyrolytic carbon and glassy carbon structures formed by the aromatic resin to have high adhesion to the underlying layer, and to form air-insulating protection for the underlying silicone epoxy resin, so that the silicone epoxy resin can better undergo a ceramic transformation under high temperature conditions, thereby exhibiting better high temperature resistance and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the structure of silicone epoxy coating.

[0034] Figure 2 Schematic diagram of the graphene modified gradient distribution coating structure. DETAILED DESCRIPTION

[0035] Example 1

[0036] The anticorrosion coating formula of the present invention is as follows:

[0037] Base material formula: 70kg silicone hybrid epoxy resin, 2kg n-butanol, 3kg butyl acetate, 10kg hollow glass microspheres, 8kg titanium dioxide, 5kg mica iron oxide, and 2kg modified bentonite.

[0038] Additive formula: C9 aromatic resin 14.5kg, xylene 14.5kg, graphene oxide 0.5kg, fumed silica 0.5kg

[0039] Curing agent formula: 17.5kg 3-aminopropyltriethylsilane, 0.5kg n-butanol.

[0040] The preparation method of the anticorrosion coating of the present invention:

[0041] 0.5 g of graphene oxide, 5 g of silane coupling agent γ-aminopropyltriethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 150 W for 30 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 50 ° C constant temperature oil bath and stirred for 14 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 6 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 45 ° C and dried for 10 hours to obtain silane-modified graphene oxide.

[0042] 70kg of organosilicon hybrid epoxy resin, 2kg of n-butanol, 3kg of butyl acetate, 10kg of hollow glass microspheres, 8kg of titanium dioxide, 5kg of mica iron oxide, and 2kg of modified bentonite were added to the reaction container in sequence, and stirred at 600r / min for 20 minutes at room temperature to obtain the base material; 14.5kg of aromatic hydrocarbon resin, 14.5kg of xylene, 0.5kg of modified graphene, and 0.5kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under the condition of a constant temperature oil bath at 80°C to obtain the additive; 17.5kg of 3-aminopropyltriethylsilane and 0.5kg of n-butanol were added to another reaction container in sequence, and stirred at 500r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 30kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 18 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0043] The coating was applied to the surface of the substrate by brushing, cured at room temperature for 24 hours to obtain a coating film, heated from room temperature to 500°C at a heating rate of 5°C / min, and maintained at 500±10°C for 2 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0044] Example 2

[0045] The anticorrosion coating formula of the present invention is as follows:

[0046] Base material formula: 60kg silicone hybrid epoxy resin, 4.5kg n-butanol, 4kg butyl acetate, 12.5kg hollow glass microspheres, 12.5kg titanium dioxide, 5kg mica iron oxide, and 1.5kg modified bentonite.

[0047] Additive formula: C5 petroleum resin 12kg, xylene 17kg, modified graphene 0.5kg, fumed silica 0.5kg

[0048] Curing agent formula: 15kg 3-aminopropyltriethylsilane, 1kg n-butanol.

[0049] The preparation method of the anticorrosion coating of the present invention:

[0050] 0.75 g of graphene oxide, 10 g of silane coupling agent vinyl triethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 200 W for 30 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 15 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 5 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 55 ° C and dried for 12 hours to obtain silane-modified graphene oxide.

[0051] 60kg of organosilicon hybrid epoxy resin, 4.5kg of n-butanol, 4kg of butyl acetate, 12.5kg of hollow glass microspheres, 12.5kg of titanium dioxide, 5kg of mica iron oxide, and 1.5kg of modified bentonite were added to the reaction container in sequence, and stirred at 600r / min for 20 minutes at room temperature to obtain the base material; 12kg of C5 petroleum resin, 17kg of xylene, 0.5kg of graphene oxide, and 0.5kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under the condition of a constant temperature oil bath at 80°C to obtain the additive; 15kg of 3-aminopropyltriethylsilane and 1kg of n-butanol were added to another reaction container in sequence, and stirred at 500r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 30kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 16 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0052] The coating was applied to the surface of the metal substrate by brushing, cured at room temperature for 30 hours to obtain a coating film, heated from room temperature to 500°C at a heating rate of 10°C / min, and maintained at 500±10°C for 3 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0053] Example 3

[0054] The anticorrosion coating formula of the present invention is as follows:

[0055] Base material formula: 64kg silicone hybrid epoxy resin, 3kg n-butanol, 3kg butyl acetate, 13.5kg hollow glass microspheres, 10kg titanium dioxide, 5kg mica iron oxide, and 1.5kg modified bentonite.

[0056] Additive formula: 16kg hydrogenated petroleum resin, 14kg xylene, 0.5kg graphene oxide, 0.5kg fumed silica

[0057] Curing agent formula: 16kg 3-aminopropyltriethylsilane, 1kg n-butanol.

[0058] The preparation method of the anticorrosion coating of the present invention:

[0059] 0.7 g of graphene oxide, 8 g of silane coupling agent γ-glycidyloxypropyltrimethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 200 W for 30 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 15 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.35 μm, and washed 10 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 50 ° C and dried for 16 hours to obtain silane-modified graphene oxide.

[0060] 64kg of organosilicon hybrid epoxy resin, 3kg of n-butanol, 3kg of butyl acetate, 13.5kg of hollow glass microspheres, 10kg of titanium dioxide, 5kg of mica iron oxide, and 1.5kg of modified bentonite were added to the reaction container in sequence, and stirred at 600r / min for 25 minutes at room temperature to obtain the base material; 16kg of hydrogenated petroleum resin, 14kg of xylene, 0.5kg of graphene oxide, and 0.5kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under the condition of a constant temperature oil bath at 80°C to obtain the additive; 16kg of 3-aminopropyltriethylsilane and 1kg of n-butanol were added to another reaction container in sequence, and stirred at 500r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 31kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 17 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0061] The coating was applied to the surface of the metal substrate by spraying, cured at room temperature for 48 hours to obtain a coating film, and the temperature was increased from room temperature to 500°C at a heating rate of 10°C / min, and maintained at 500±10°C for 4 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0062] Example 4

[0063] The anticorrosion coating formula of the present invention is as follows:

[0064] Base material formula: 68kg silicone hybrid epoxy resin, 2.5kg n-butanol, 3kg butyl acetate, 13.5kg hollow glass microspheres, 9kg titanium dioxide, 3.5kg mica iron oxide, and 0.5kg modified bentonite.

[0065] Additive formula: C9 aromatic resin 17kg, xylene 13kg, graphene oxide 0.7kg, fumed silica 1.8kg

[0066] Curing agent formula: 17kg 3-aminopropyltriethylsilane, 1kg n-butanol.

[0067] The preparation method of the anticorrosion coating of the present invention:

[0068] 0.8 g of graphene oxide, 10 g of silane coupling agent vinyl triethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 300 W for 20 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 18 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 8 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 55 ° C and dried for 20 hours to obtain silane-modified graphene oxide.

[0069] 68kg of organosilicon hybrid epoxy resin, 2.5kg of n-butanol, 3kg of butyl acetate, 13.5kg of hollow glass microspheres, 9kg of titanium dioxide, 3.5kg of mica iron oxide, and 0.5kg of modified bentonite were added to the reaction container in sequence, and stirred at 600r / min for 25 minutes at room temperature to obtain the base material; 17kg of C9 aromatic resin, 13kg of xylene, 0.7kg of graphene oxide, and 1.8kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under a constant temperature oil bath at 80°C to obtain the additive; 17kg of 3-aminopropyltriethylsilane and 1kg of n-butanol were added to another reaction container in sequence, and stirred at 500r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 32.5kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 18 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0070] The coating was applied to the surface of the metal substrate by spraying, cured at room temperature for 48 hours to obtain a coating film, and the temperature was increased from room temperature to 500°C at a heating rate of 10°C / min, and maintained at 500±10°C for 5 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0071] Example 5

[0072] The anticorrosion coating formula of the present invention is as follows:

[0073] Base material formula: 60kg silicone hybrid epoxy resin, 4kg n-butanol, 3.5kg butyl acetate, 15kg hollow glass microspheres, 10.5kg titanium dioxide, 6kg mica iron oxide, and 1kg modified bentonite.

[0074] Additive formula: C9 aromatic resin 14.5kg, xylene 14kg, graphene oxide 1kg, fumed silica 1.5kg

[0075] Curing agent formula: 15kg 3-aminopropyltriethylsilane, 1kg n-butanol.

[0076] The preparation method of the anticorrosion coating of the present invention:

[0077] 0.9 g of graphene oxide, 9 g of silane coupling agent γ-aminopropyltriethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 240 W for 30 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 15 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 5 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 50 ° C and dried for 12 hours to obtain silane-modified graphene oxide.

[0078] 60kg of organosilicon hybrid epoxy resin, 4kg of n-butanol, 3.5kg of butyl acetate, 15kg of hollow glass microspheres, 10.5kg of titanium dioxide, 6kg of mica iron oxide, and 1kg of modified bentonite were added to the reaction container in sequence, and stirred at 600r / min for 25 minutes at room temperature to obtain the base material; 14.5kg of C9 aromatic resin, 14kg of xylene, 1kg of graphene oxide, and 1.5kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under a constant temperature oil bath at 80°C to obtain the additive; 15kg of 3-aminopropyltriethylsilane and 1kg of n-butanol were added to another reaction container in sequence, and stirred at 500r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 31kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 16 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0079] The coating was applied to the surface of the metal substrate by brushing, cured at room temperature for 36 hours to obtain a coating film, and the temperature was increased from room temperature to 500°C at a heating rate of 8°C / min, and maintained at 500±10°C for 4.5 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0080] Example 6

[0081] The anticorrosion coating formula of the present invention is as follows:

[0082] Base material formula: 70kg silicone hybrid epoxy resin, 2.5kg n-butanol, 3kg butyl acetate, 10.5kg hollow glass microspheres, 9kg titanium dioxide, 4.5kg mica iron oxide, and 0.5kg modified bentonite.

[0083] Additive formula: C9 aromatic resin 15.5kg, xylene 13kg, graphene oxide 0.8kg, fumed silica 0.7kg

[0084] Curing agent formula: 17.5kg 3-aminopropyltriethylsilane, 1.5kg n-butanol.

[0085] The preparation method of the anticorrosion coating of the present invention:

[0086] 0.75 g of graphene oxide, 10 g of silane coupling agent γ-aminopropyltriethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 200 W for 25 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 15 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 6 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 60 ° C and dried for 16 hours to obtain silane-modified graphene oxide.

[0087] 70kg of organosilicon hybrid epoxy resin, 2.5kg of n-butanol, 3kg of butyl acetate, 10.5kg of hollow glass microspheres, 9kg of titanium dioxide, 4.5kg of mica iron oxide, and 0.5kg of modified bentonite were added to the reaction container in sequence, and stirred at 500r / min for 30 minutes at room temperature to obtain the base material; 15.5kg of C9 aromatic resin, 13kg of xylene, 0.8kg of graphene oxide, and 0.7kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under a constant temperature oil bath at 80°C to obtain the additive; 17.5kg of 3-aminopropyltriethylsilane and 1.5kg of n-butanol were added to another reaction container in sequence, and stirred at 550r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 30kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 19 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0088] The coating was applied to the surface of the metal substrate by spraying, cured at room temperature for 48 hours to obtain a coating film, and the temperature was increased from room temperature to 500°C at a heating rate of 10°C / min, and maintained at 500±10°C for 5 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0089] After the base material and additives are mixed and stirred, the curing agent should be added within 3 hours to prepare the coating. The effective use time after the three components are mixed shall not exceed 2 hours.

[0090] Comparative Example 1

[0091] The anticorrosion coating formula of the present invention is as follows:

[0092] Base material formula: 60kg silicone hybrid epoxy resin, 4kg n-butanol, 3.5kg butyl acetate, 15kg hollow glass microspheres, 10.5kg titanium dioxide, 6kg mica iron oxide, and 1kg modified bentonite.

[0093] Additive formula: 14kg xylene, 0.5kg graphene oxide, 1.5kg fumed silica

[0094] Curing agent formula: 15kg 3-aminopropyltriethylsilane, 1kg n-butanol.

[0095] The preparation method of the anticorrosion coating of the present invention:

[0096] 0.9 g of graphene oxide, 9 g of silane coupling agent γ-aminopropyltriethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 240 W for 30 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 15 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 5 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 50 ° C and dried for 12 hours to obtain silane-modified graphene oxide.

[0097] 60kg of organosilicon hybrid epoxy resin, 4kg of n-butanol, 3.5kg of butyl acetate, 15kg of hollow glass microspheres, 10.5kg of titanium dioxide, 6kg of mica iron oxide, and 1kg of modified bentonite were added to the reaction container in sequence, and stirred at 600r / min for 25 minutes at room temperature to obtain the base material; 14kg of xylene, 0.5kg of graphene oxide, and 1.5kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under a constant temperature oil bath at 80°C to obtain the additive; 15kg of 3-aminopropyltriethylsilane and 1kg of n-butanol were added to another reaction container in sequence, and stirred at 500r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 16kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 16 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0098] The coating was applied to the surface of the metal substrate by brushing, cured at room temperature for 36 hours to obtain a coating film, and the temperature was increased from room temperature to 500°C at a heating rate of 8°C / min, and maintained at 500±10°C for 4.5 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0099] Comparative Example 2

[0100] The anticorrosion coating formula of the present invention is as follows:

[0101] Base material formula: 70kg silicone hybrid epoxy resin, 2.5kg n-butanol, 3kg butyl acetate, 10.5kg hollow glass microspheres, 9kg titanium dioxide, 4.5kg mica iron oxide, and 0.5kg modified bentonite.

[0102] Additive formula: C9 aromatic resin 16.5kg, xylene 13kg, fumed silica 0.5kg

[0103] Curing agent formula: 17.5kg 3-aminopropyltriethylsilane, 1.5kg n-butanol.

[0104] The preparation method of the anticorrosion coating of the present invention:

[0105] 0.75 g of graphene oxide, 10 g of silane coupling agent γ-aminopropyltriethoxysilane, 10 g of deionized water, and 100 g of anhydrous ethanol were added to a container and ultrasonically treated at 200 W for 25 minutes to obtain a graphene oxide dispersion. The dispersion was then placed in a 60 ° C constant temperature oil bath and stirred for 15 hours to obtain a modified graphene oxide solution. The graphene solution was filtered using a microporous membrane with a pore size of 0.25 μm, and washed 6 times with anhydrous ethanol. Finally, the modified graphene oxide wet cake was placed in a vacuum drying oven at 60 ° C and dried for 16 hours to obtain silane-modified graphene oxide.

[0106] 70kg of organosilicon hybrid epoxy resin, 2.5kg of n-butanol, 3kg of butyl acetate, 10.5kg of hollow glass microspheres, 9kg of titanium dioxide, 4.5kg of mica iron oxide, and 0.5kg of modified bentonite were added to the reaction container in sequence, and stirred at 500r / min for 30 minutes at room temperature to obtain the base material; 16.5kg of C9 aromatic resin, 13kg of xylene, and 0.5kg of fumed silica were added to the container in sequence, and stirred at 300r / min for 1 hour under the condition of 80℃ constant temperature oil bath to obtain the additive; 17.5kg of 3-aminopropyltriethylsilane and 1.5kg of n-butanol were added to another reaction container in sequence, and stirred at 550r / min for 5 minutes at room temperature to obtain the curing agent. 100kg of the base material and 30kg of the additive were mixed, and stirred at 500r / min for 25 minutes at room temperature. Finally, 19 kg of curing agent was added and mixed, and stirred at a speed of 500 r / min at room temperature for 10 minutes to obtain a graphene high temperature resistant and anti-corrosion coating.

[0107] The coating was applied to the surface of the metal substrate by spraying, cured at room temperature for 48 hours to obtain a coating film, and the temperature was increased from room temperature to 500°C at a heating rate of 10°C / min, and maintained at 500±10°C for 5 hours to obtain a gradient-distributed high-temperature resistant anti-corrosion coating.

[0108] After the base material and additives are mixed and stirred, the curing agent should be added within 3 hours to prepare the coating. The effective use time after the three components are mixed shall not exceed 2 hours.

[0109] The various properties of the new high temperature resistant anti-corrosion coating are shown in Table 1 below.

[0110] Table 1 Test results of various properties of new high temperature resistant anticorrosion coating

[0111]

[0112]

[0113]

[0114] In summary, through the comparison of the examples and comparative examples in Table 1, C9 aromatic resin and graphene oxide are added to the coating as additives, which can not only improve the mechanical properties of the coating in various aspects, but also significantly improve the heat resistance and corrosion resistance of the coating. The fundamental reason is that the C9 aromatic resin forms a gradient distribution protective layer during the high-temperature curing process, and the graphene connects the aromatic resin and the matrix resin, so that the two form a good connection and strengthen the protection of the aromatic resin, thereby improving the high temperature resistance of the coating while also improving the corrosion resistance of the coating. Figure 1 Schematic diagram of curing of a coating without adding aromatic hydrocarbon resin and graphene in a comparative example; Figure 2 The schematic diagram of curing of the coating to which the aromatic hydrocarbon resin and graphene are added in the present invention shows that during the curing process, the aromatic hydrocarbon resin forms a gradient distribution protective layer on the surface of the coating, and the graphene strengthens the interface connection between the aromatic hydrocarbon resin and the matrix resin.

[0115] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Graphene modified gradient distribution high temperature resistant anticorrosion coating, characterized in that: The anticorrosive coating comprises a graphene thermoplastic resin additive, an organosilicon hybrid epoxy resin base material and a curing agent; the mass fractions of the graphene thermoplastic resin additive component are: 45 to 59 parts of xylene, 40 to 50 parts of aromatic hydrocarbon resin, 0.05 to 1 part of modified graphene oxide, and 0.5 to 2.5 parts of fumed silica.

2. The graphene-modified gradient-distributed high-temperature-resistant anticorrosion coating according to claim 1, characterized in that: The mass fractions of the organosilicon hybrid epoxy resin base material components are: 50-80 parts of organosilicon hybrid epoxy resin, 1-5 parts of n-butanol, 1-5 parts of butyl acetate, 5-20 parts of hollow glass microspheres, 3-15 parts of titanium dioxide, 3-15 parts of mica iron oxide, and 0.5-8 parts of modified bentonite.

3. The graphene-modified gradient-distributed high-temperature-resistant anticorrosion coating according to claim 1, characterized in that: The mass fractions of the aminosilane curing agent component are: 1 to 5 parts of n-butanol, 1 to 5 parts of butyl acetate, and 90 to 98 parts of aminosilane coupling agent.

4. The method for preparing the graphene-modified gradient-distributed high-temperature-resistant anticorrosion coating according to claim 1, characterized in that: The steps include: Step 1: adding graphene oxide, anhydrous ethanol and a silane coupling agent to deionized water, ultrasonically treating at a power of 100 to 300 W for 10 to 30 minutes to obtain a graphene oxide dispersion; placing the dispersion in a constant temperature oil bath at 50 to 80° C. and continuously stirring for 12 to 24 hours to obtain a modified graphene oxide solution; filtering the modified graphene oxide solution using a microporous membrane with a pore size of 0.25 to 0.5 μm, and washing with anhydrous ethanol for 5 to 10 times, and finally placing the modified graphene oxide wet cake in a vacuum drying oven at 40 to 60° C. and drying for 5 to 10 hours to obtain silane-modified graphene oxide; Step 2: adding the silane-modified graphene oxide to a xylene solution, treating it under an ultrasonic action of 100 to 300 W for 0.5 hours to obtain a graphene oxide dispersion, then adding an aromatic hydrocarbon resin and an oleophilic fumed silica, and continuously stirring the mixture at a speed of 300 to 600 r / min for 0.5 to 2 hours in a constant temperature oil bath at 50 to 80° C. to obtain an additive; Step 3: Mix the components of the organosilicon hybrid epoxy resin base material, and continuously stir at a speed of 300 to 600 r / min for 15 to 60 minutes at room temperature to obtain a base material; Step 4: Mix the additive with the base material, stir continuously at a speed of 300 to 600 r / min for 15 to 60 minutes at room temperature, finally add the curing agent components, and stir continuously at a speed of 300 to 600 r / min for 15 to 30 minutes at room temperature to obtain a high temperature resistant anticorrosion coating; Step 5: Apply the above-mentioned high temperature resistant anti-corrosion coating on the substrate, dry it at room temperature for 12 to 60 hours to form a cured coating film, then increase the temperature from room temperature to 400 to 700°C at a heating rate of 3 to 15°C / min, and maintain it at 400 to 700±10°C for 2 to 8 hours to obtain a gradient distributed high temperature resistant anti-corrosion coating.

5. The preparation method according to claim 4, characterized in that: The amount of the additive in step 4 is 20% to 40% of the base material.

6. The preparation method according to claim 4, characterized in that: The amount of the additive in step 4 is 25% to 35% of the base material.

7. The preparation method according to claim 4, 5 or 6, characterized in that: In step 4, the amount of curing agent used should be 22.5% to 30% of the base material.

8. The preparation method according to claim 4, 5 or 6, characterized in that: The graphene oxide described in step 1 is lightly oxidized graphene, having 1 to 5 layers, a lateral equivalent diameter of the flakes of 0.5 to 5 μm, oxygen-containing groups of hydroxyl, carboxyl, and epoxy groups, or a combination thereof, and an oxygen-carbon ratio of 0.1 to 2; the silane coupling agent is selected from one or any combination of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

9. The preparation method according to claim 4, 5 or 6, characterized in that: In step 1, the amount of graphene oxide used is 0.1% to 1% of the amount of anhydrous ethanol used; the amount of silane coupling agent used is 0.1% to 10% of the amount of anhydrous ethanol used; and the amount of water used is 5% to 100% of the amount of anhydrous ethanol used.

10. The preparation method according to claim 4, 5 or 6, characterized in that: In step 2, the aromatic hydrocarbon resin includes but is not limited to one or a mixture of C5 aliphatic petroleum resin, C9 aromatic petroleum resin, DCPD cycloaliphatic diene resin, hydrogenated petroleum resin, and condensed polynuclear aromatic hydrocarbon resin; the primary particle size of the oleophilic fumed silica is 10 to 40 nm, and the surface grafted modifier includes but is not limited to one or a combination of the following: polydimethylsiloxane, dimethyldichlorosilane, hexamethyldisilazane, γ-aminopropyltriethoxysilane, and trimethoxypropylaminosilane.

Citation Information

Patent Citations

  • Graphene oxide modified waterborne epoxy primer for heavy-duty corrosion protection and preparation method thereof

    CN109504233A

  • Graphene modified high chlorinated polyethylene resin anticorrosive paint and preparation method thereof

    CN111909573A

  • Solvent-free graphene metal anticorrosive paint and preparation method thereof

    CN118085677A

  • Graphene paint

    WO2023090990A1

Cited By

  • Petroleum aromatic resin modified phase transformation protective coating and preparation method thereof

    CN120944451A

  • A phase transition protective coating modified with petroleum aromatic resin and its preparation method

    CN120944451B